2023
DOI: 10.1039/d3nj01411h
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic six-coordinate bismuth(iii) complexes with 2-acetylthiophene thiosemicarbazones: synthesis, characterization, and biological properties

Abstract: The present study aimed to prepare and then evaluate the antiproliferative and antibacterial activities of bismuth(III) thiosemicarbazone complexes. Five bismuth(III) halide complexes of general formulae [BiX3(HL)3] (X: Cl; 1 and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…For example, Ozturk et al reported recently several Bi 3+ coordinated in an S-monodentate fashion to thiosemicarbazone and other ligands, finding that most of them give no significative cytotoxicity against MCF-7 cells, IC 50 (48 h) > 30 µM, and some of them presented moderate activity, IC 50 (48 h) = 5.4-8.0 µM, against this cancer cell line [154][155][156][157]. Very recently, this research group reported five Bi 3+ halide complexes with thiosemicarbazone bearing an acetylthiophene moiety that presented moderate cytotoxicity on HeLa cells (IC 50 4.5-24.3 µM) [158]. They also reported several Bi 3+ complexes coordinated in an S-monodentate mode to thioamide ligands that showed low to moderate activity against human adenocarcinoma cells, HeLa (cervix) and MCF-7 (breast), with most IC 50 (48 h) values superior to 30 µM [159,160].…”
Section: Bismuth(iii) Complexes Bearing S-donor Ligandsmentioning
confidence: 99%
“…For example, Ozturk et al reported recently several Bi 3+ coordinated in an S-monodentate fashion to thiosemicarbazone and other ligands, finding that most of them give no significative cytotoxicity against MCF-7 cells, IC 50 (48 h) > 30 µM, and some of them presented moderate activity, IC 50 (48 h) = 5.4-8.0 µM, against this cancer cell line [154][155][156][157]. Very recently, this research group reported five Bi 3+ halide complexes with thiosemicarbazone bearing an acetylthiophene moiety that presented moderate cytotoxicity on HeLa cells (IC 50 4.5-24.3 µM) [158]. They also reported several Bi 3+ complexes coordinated in an S-monodentate mode to thioamide ligands that showed low to moderate activity against human adenocarcinoma cells, HeLa (cervix) and MCF-7 (breast), with most IC 50 (48 h) values superior to 30 µM [159,160].…”
Section: Bismuth(iii) Complexes Bearing S-donor Ligandsmentioning
confidence: 99%
“…Thiosemicarbazones are a class of N, S-donor ligands that have been widely employed in coordination chemistry because of their structural adaptability and versatility, since they can exist as thione-thiol tautomers, and accordingly, can bind to metal centres as monodentate, bidentate, or bridging ligands. 1,2 Due to their pharmacological characteristics, particularly as antiphrastic, antibacterial, antioxidant, and anticancer agents, thiosemicarbazone derivatives and their metal complexes have attracted significant interest in chemistry and biology. 3–8 Specifically, heterocyclic thiosemicarbazones derived by condensation between the carbonyl of a heterocyclic moiety and thiosemicarbazide can form pincer-type complexes with suitable metal ions, as they can act as O,N,S- or N,N,S-donor chelating ligands.…”
Section: Introductionmentioning
confidence: 99%